An Osteolytic Metastasis of Humerus from an Asymptomatic Squamous Cell Carcinoma of Lung: A Rare Clinical Entity - Anirban Das; Sudipta Pandit; Sibes k. Das; Sumitra Basuthakur; Somnath Das (Case Reports in Pulmonology)
Advanced lung cancer is complicated by skeletal metastases either due to direct extension from adjacent primaries or, more commonly, due to haematogenous dissemination of neoplastic cells. Lumber spine is the most common site for bony metastases in bronchogenic carcinoma. Proximal lone bones, especially humerus, are unusual sites for metastases from lung primaries. Small cell and large cell varieties of lung cancer are most commonly associated with skeletal dissemination. It is also unusual that an asymptomatic squamous cell carcinoma of lung presents with painful, soft tissue swelling with osteolytic metastasis of humerus which is reported in our case. Systemic cytotoxic chemotherapy, local palliative radiotherapy, adequate analgesia, and internal fixation of the affected long bone are different modalities of treatment in this advanced stage of disease. But the prognosis is definitely poor in this stage IV disease.